An Analysis of Social Deixis in Duduk Atas Village - Fitri Arniati (Insan Kreasi Media, 2025)
This research analyzes the types and causes of social deixis used in Duduk Atas Village, West Lombok. Social deixis refers to linguistic expressions that encode social relationships between speakers and addressees. Using a descriptive qualitative method, the researcher collected data through observation, interviews, questionnaires, and note-taking from speakers across five areas of the village. The findings show that the community employs a wide range of social deixis depending on age groups, social status, occupation, religious achievements, and peer relationships. Social deixis used among children includes side and meq/ante, while among teenagers additional forms such as kak tuan/tuanno, bapak, and jejalek appear based on social status and friendship circles. Adults use deixis such as wayahanno, mamiq, and bapak, while elderly individuals are referred to using niniq and puk tuan as markers of respect. General deixis such as ne, ie, and mbilinan are used across all age groups. The study concludes that variations in social deixis are influenced by age, social hierarchy, religious status, jobs, and interpersonal relationships. These findings highlight the importance of social deixis as a sociolinguistic system that shapes politeness, social identity, and communication patterns in the Sasak-speaking community of Duduk Atas Village.